Regulation of nisin biosynthesis and immunity in Lactococcus lactis 6F3. - Engelke, G (1994)
The biosynthetic genes of the nisin-producing strain Lactococcus lactis 6F3 are organized in an operon-like structure starting with the structural gene nisA followed by the genes nisB, nisT, and nisC, which are probably involved in chemical modification and secretion of the prepeptide (G. Engelke, Z. Gutowski-Eckel, M. Hammelmann, and K.-D. Entian, Appl. Environ. Microbiol. 58:3730-3743, 1992). Subcloning of an adjacent 5-kb downstream region revealed additional genes involved in nisin biosynthesis. The gene nisI, which encodes a lipoprotein, causes increased immunity after its transformation into nisin-sensitive L. lactis MG1614. It is followed by the gene nisP, coding for a subtilisin-like serine protease possibly involved in processing of the secreted leader peptide. Adjacent to the 3' end of nisP the genes nisR and nisK were identified, coding for a regulatory protein and a histidine kinase, showing marked similarities to members of the OmpR/EnvZ-like subgroup of two-component regulatory systems. The deduced amino acid sequences of nisR and nisK exhibit marked similarities to SpaR and SpaK, which were recently identified as the response regulator and the corresponding histidine kinase of subtilin biosynthesis. By using antibodies directed against the nisin prepeptide and the NisB protein, respectively, we could show that nisin biosynthesis is regulated by the expression of its structural and biosynthetic genes. Prenisin expression starts in the exponential growth phase and precedes that of the NisB protein by approximately 30 min. Both proteins are expressed to a maximum in the stationary growth phase.